1980
DOI: 10.1093/brain/103.2.413
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Nature of Visual Pathway Involvement in Friedreich's Ataxia

Abstract: Pattern-reversal visual evoked potentials (VEP) were recorded from 22 patients (mean age 33.7 years) with Friedreich's ataxia, 15 of whom also had a detailed neuro-ophthalmological assessment prior to the VEP examination. None had noted symptomatic visual impairment. Eleven of the 15 (73 per cent) examined clinically had one or more neuro-ophthalmic abnormality and 14/22 (64 per cent) had an abnormal VEP study which was always binocular and comprised absent responses, or most commonly, increased P100 component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0
1

Year Published

1981
1981
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(48 citation statements)
references
References 0 publications
5
42
0
1
Order By: Relevance
“…Evidence of optic neuropathy is present in up to two-thirds of cases of Friedreich's ataxia, although severe visual loss is uncommon. [168][169][170][171][172][173][174] A condition resembling Friedreich's ataxia associated with decreased vitamin E levels has been localized to chromosome 8, and also includes some patients with optic atrophy. 175 Vitamin E supplementation of these patients may be efficacious early in the course of the disease.…”
Section: Optic Neuropathy As a Manifestation Of Hereditary Degeneratimentioning
confidence: 99%
“…Evidence of optic neuropathy is present in up to two-thirds of cases of Friedreich's ataxia, although severe visual loss is uncommon. [168][169][170][171][172][173][174] A condition resembling Friedreich's ataxia associated with decreased vitamin E levels has been localized to chromosome 8, and also includes some patients with optic atrophy. 175 Vitamin E supplementation of these patients may be efficacious early in the course of the disease.…”
Section: Optic Neuropathy As a Manifestation Of Hereditary Degeneratimentioning
confidence: 99%
“…As far as optic disc pallor is concerned, Heck [11] found no optic nerve fiber atrophy while Geoffroy et al [10] observed it in 50% of their cases. More recently Carrol et al [4] have reported disc pallor in 11 out of 15 patients. In the course of the present study, we have compared traditional ophthal moscopy with red-free light retinography; our data lead us to conclude that a lack of disc pallor cannot in itself be interpreted as an absence of nerve fiber degeneration.…”
Section: Discussionmentioning
confidence: 91%
“…Electroretinal function is commonly assessed by re cording responses to flash or pattern stimuli. The few flash ERG studies carried out on a small number o f'typ ical' FA subjects have produced results variously re ported as 'normal' [21] 'subnormal' [4] or 'abnormal' [15]. These last investigators have published the only FA study using PERG [ 15], In 7 out of their 9 cases they found reduced amplitudes but normal latencies; how ever they failed to describe these changes in detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frataxin is a mitochondrial protein involved in Fe-S cluster assembly, disruption of which results in excessive mitochondrial iron levels and loss of retinal ganglion cells, giving rise to optic neuropathy and ataxia. 2,4,97 The oxidative phosphorylation pathway relies on the redox ability of Fe, via multiple Fe-S clusters, to perform electron transfer and thus energy transduction. Four of the five oxidative phosphorylation complexes contain either or both heme prosthetic groups or Fe-S clusters.…”
Section: Mendelian Mitochondrial Syndromes With Ocular Involvementmentioning
confidence: 99%